Simulasi Pembebanan Komponen Bender pada Desain Mesin Begel Fabricator Menggunakan Software Autodesk Inventor 2020 - Hariyanto, Satriawan Dini; Kurniawan, Wikan (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2021)
Stress analysis of the bender components in the design of the begel fabricator machine was carried out using FEA (Finite Element Analysis) with three variations of the constituent material parameters, namely 6061 aluminum, mild steel, and cast iron with a modulus of elasticity of 68.9 GPa, 220 GPa, 120.5 GPa, respectively. The test is carried out by a loading parameter 2520 MPa and fixed constraint. The maximum von misses stress and displacement obtained for each material parameter components using aluminum, mild steel, and cast iron are 17.78 MPa; 0.00765, 17.49 MPa; 0.00229, 17.62 MPa; 0.00427 respectively.